(untitled) (Letters in Nonlinear Analysis and its Applications, 2025)
The purpose of this brief note is to correct and clarify a wrong assertion given in the recent article "Some Applications of the Weak Contraction Principle" [Lett. Nonlinear Anal. Appl. 3 (2025), 1-4], that affects both a valid example used in the article "Remarks on the fixed point theory for quasi-metric spaces" [Results Nonlinear Anal. 7 (2024), 70–74], and two incorrect results presented in the article "All metric fixed point theorems hold for quasi-metric spaces" [Results Nonlinear Anal. 6 (2023), 116–127].